ZBTB33 Is Mutated in Clonal Hematopoiesis and Myelodysplastic Syndromes and Impacts RNA Splicing - Beauchamp, Ellen M.; Leventhal, Matthew; Bernard, Elsa; Hoppe, Emma R.; Todisco, Gabriele; Creignou, Maria; Gallì, Anna; Castellano, Cecilia A.; McConkey, Marie; Tarun, Akansha; Wong, Waihay; Schenone, Monica; et al. (Blood cancer discovery, 2021)
Clonal hematopoiesis results from somatic mutations in cancer driver genes in hematopoietic stem cells. We sought to identify novel drivers of clonal expansion using an unbiased analysis of sequencing data from 84,683 persons and identified common mutations in the 5-methylcytosine reader, , as well as in , , and . We also identified these mutations at low frequency in myelodysplastic syndrome patients. edited mouse hematopoietic stem and progenitor cells exhibited a competitive advantage and increased genome-wide intron retention. mutations potentially link DNA methylation and RNA splicing, the two most commonly mutated pathways in clonal hematopoiesis and MDS.